The essence of care in health vulnerability: a Heideggerian construction - Virna Ribeiro Feitosa Cestari; Thereza Maria Magalhães Moreira; Vera Lúcia Mendes de Paula Pessoa; Raquel Sampaio Florêncio; Maria Rocineide Ferreira da Silva; Raimundo Augusto Martins Torres
ABSTRACT Objective: Reflect on the essence of care in health vulnerability from the phenomenological perspective of Martin Heidegger. Method: Theoretical-reflexive study, anchored in three essential parts: 1) Care in Heidegger; 2) The essence of care in health vulnerability; And 3) Nursing care actions on health vulnerability. Results: Vulnerability must be recognized as an indelible trait of the human condition and has its constituents in the human being, co-presence and care. Caring is an interactive process that reveals itself in the relationship with the other. Respecting the integrity of the Being in vulnerability must be a priority in nursing care, through behaviors that privilege the Being. Conclusion: Understanding ontological care and its relation to vulnerability under Heidegger's phenomenological view allowed us to uncover the facets of care in health vulnerability by adding to the nursing knowledge body a comprehensive and reflective perspective.